A Comprehensive Review on Sustainable Energy Source - Kiran Patel (International Journal of Scientific Research in Science and Technology, 2025)
The article examines different methodologies employed for the generation of electric power from renewable energy sources, applicable for integration with a power grid and for operation as a standalone system. All renewable energy resources, with the exception of geothermal energy, are dependent on climatic conditions. Consequently, the power generated from these sources varies in magnitude and may occasionally result in no power generation at all. This paper reviews various schemes outlined in the literature aimed at enhancing power quality and overall system performance through the application of advanced power electronics technologies. This document provides a detailed analysis of significant sustainable energy technologies pertinent to India and the international landscape: solar photovoltaic (PV), onshore wind, hydropower (both large and small scale), biomass and waste-to-energy, concentrating solar power (CSP), as well as emerging alternatives such as offshore wind, geothermal, and hydrogen. Each technology is summarized with respect to its construction and operational principles, typical advantages and disadvantages, applications in India, and essential technical and economic parameters.
Keywords: Solar PV; WECS; CSP; renewable energy; power generation; atmosphere condition